Spatial Distribution of Tuberculosis Disease in Varanasi District: A Case Study in Health Geography - Giri, Ajay Kumar; Srivastva, G.N.; Mishra, A.P. (National Geographical Journal of India, 2022)
Health gets the most prominent place in one's life and is the measure of an individual's well being. According to WHO, "health is a state of complete physical, mental and social well being and not merely the absence of disease or infirmity and it is vital for ethical, artistic, material and spiritual development of man. Tuberculosis, a chronic disease, is raising its head as the most threatening health menace in the developing countries, particularly in India. The poor people are more vulnerable to this pandemic, One out of every three Indians are infected with it. According to a report, tuberculosis kills more adults in India than HIV, STD, Malaria, leprosy, and other tropical diseases combined. Tuberculosis not only impacts upon one's health, but it also brings in miserable living, challenges the livelihood and poses social problems. Considering these aspects, now it is a national priority within the health sectors. But an irony that in spite of adoption of National Tuberculosis Programme (NTP) way back in 1962 (revised in 1992 as Revised National Tuberculosis Control Programme (RNTCP) and in 1993, as a comprehensive strategy for TB control in India, the health sector has failed to achieve its desired goals even today! Tuberculosis has spread its wings in almost all the district of India and Varanasi is no exception to it. This study is an attempt to reflect the state of Tuberculosis in Varanasi district with respect to spatio-temporal dimensions. This paper studies and analyses the distribution of tuberculosis patients in seven units on the basis of seven indicators i.e., New Smear Positive, New Smear Negative, Extrapulmonary, Relapse, Failure, Treatment after Default, and others. This study is based on secondary sources of data.